Development of Contextual Triangles and Quadrilaterals Worksheets for 7th Graders - Wisnu Siwi Satiti; Hidayatul Maslakhah; Eliza Verdianingsih (APPLICATION: Applied science in Learning Research, 2022)
Mathematics has a very important role in everyday life, where almost everything around us is related to mathematics, including culture in our society, especially concept of geometric shapes. However, the mathematics lessons that students learn at school are sometimes different from the mathematical problems encountered in everyday life, which makes it difficult for students to relate mathematical concepts to problems from real-world contexts. Therefore, teachers and educators could employ innovative and relevant teaching materials, which is also intended to increase the motivation of students to learn the theoretical material presented. Which is an abstract mathematical concept. One of teaching materials that can be used is the Student Worksheet (LKPD). In order for LKPD to be relevant to the real life of students, mathematical activities in LKPD are arranged using activities related to the daily lives of students, especially for junior high school students (SMP/MTs). Therefore, this research is about the development students’ worksheet in Triangles and Quadrilaterals concept within contextual problems for VII grade students. The type of research used is Research and Development (R&D) research, by adapting ADDIE model. The study was conducted at a class of VII at MTsN 4 Jombang. The results show that the Triangles and Quadrilaterals worksheet within contextual problems are valid and practical. Besides that, the results of the implementation of the Triangles and Quadrilaterals worksheet within contextual problems in this study showed that only focus on mathematical activities to solve procedural problems without relating them to real contexts in everyday life.